Metastasizing tenosynovial giant cell tumour, diffuse type/pigmented villonodular synovitis - Righi, A (Clin Sarcoma Res, 2015)
Tenosynovial giant cell tumour, diffuse type, also known under a variety of other terms including diffuse pigmented villonodular synovitis, tends to be locally aggressive and not infrequently can show multiple recurrences. The differential diagnosis with the extremely rare and somewhat controversial malignant variant of tenosynovial giant cell tumour, diffuse type, is challenging due to overlapping radiologic features of these two entities. Malignant tenosynovial giant cell tumour is defined by the presence of overtly malignant sarcomatous areas. We describe a very unusual case of a 63-year-old man affected by tenosynovial giant cell tumour, diffuse type of the knee that, despite absence of morphologic evidence of sarcomatous transformation, developed inguinal lymph node metastases following multiple surgical procedures.